Free Amino Acids and Sugars of Annona Squamosa Linn. - D. JOSHI, H.; A. BAXI , G.; Baxi, A.J. (Asian Journal of Chemistry, 2010)
At least nine different amino acids and three free sugars have been isolated and identified from the leaves of Annona squamosa Linn (N. O.) Annonaceae), chromatographically and their relative occurrence has been evaluated colorimetrically.